The Role of Pesantren Management in Managing Productive Waqf - Muhamad Towil Akhirudin (Proceeding of International Conference on Islamic Boarding School, 2025)
Pesantren, as an Islamic educational institution in Indonesia, has great potential in managing productive waqf; however, many still operate it consumptive. With the potential of land waqf reaching 55,259.87 hectares and cash waqf of IDR 180 trillion annually, professional management is needed to optimize waqf asset utilization. This study aims to analyse the role of pesantren management in managing productive waqf, identify factors influencing management success, and explore the impacts, challenges, and opportunities in productive waqf management. The study employs a library research methodology by analysing various literature, journals, and research related to pesantren management and productive waqf. Pesantren management plays a crucial role in implementing POAC functions (planning, organizing, activating, controlling) in productive waqf management. Internal factors affecting success include visionary leadership capacity, Nazhir professionalism, and innovation in asset management. External factors encompass regulatory support and community socio-economic conditions. Productive waqf management provides positive impacts, including improved educational infrastructure, pesantren financial independence, sustainable scholarship programs, student entrepreneurship skill development, local economic empowerment, and job creation. Implementation faces obstacles such as a lack of public understanding about productive waqf, unprofessional management, limited quality human resources, legal uncertainty of waqf asset status, and limited initial capital. There are significant opportunities for productive waqf development supported by Law No. 41 of 2004 on Waqf and BWI Regulation No. 1 of 2020, which provide a strong legal foundation and comprehensive guidelines for productive waqf management. Professional and systematic pesantren management has proven capable of optimizing waqf asset utilization to generate sustainable positive impacts for pesantren and communities. Continuous efforts to enhance management capacity and foster multi-stakeholder collaboration are needed to optimize productive waqf potential.